Sox8 and Sox9 act redundantly for ovarian-to-testicular fate reprogramming in the absence of R-spondin1 in mouse sex reversals - Nainoa Richardson; Isabelle Gillot; Elodie P Gregoire; Sameh A Youssef; Dirk de Rooij; Alain de Bruin; Marie-Cécile De Cian; Marie-Christine Chaboissier (eLife, 2020)
In mammals, testicular differentiation is initiated by transcription factors SRY and SOX9 in XY gonads, and ovarian differentiation involves R-spondin1 (RSPO1) mediated activation of WNT/β-catenin signaling in XX gonads. Accordingly, the absence of RSPO1/Rspo1 in XX humans and mice leads to testicular differentiation and female-to-male sex reversal in a manner that does not requireSry or Sox9 in mice. Here we show that an alternate testis-differentiating factor exists and that this factor is Sox8. Specifically, genetic ablation of Sox8 and Sox9 prevents ovarian-to-testicular reprogramming observed in XX Rspo1 loss-of-function mice. Consequently, Rspo1 Sox8 Sox9 triple mutant gonads developed as atrophied ovaries. Thus, SOX8 alone can compensate for the loss of SOX9 for Sertoli cell differentiation during female-to-male sex reversal.